Internal Audit as a Lever For Governance: The Case of Firms in an Emerging Economy - Elghazali Mbarka; Drissi Hicham (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Since the financial scandals of the 2000s, the business environment has been punctuated by fraud and ethical problems that increase uncertainty and risk in the conduct of business. Researchers and practitioners have analyzed these scandals as the result of the weakness and failure of corporate governance systems, including counter-powers and poor corporate governance. To cope with these slippages, we are witnessing, particularly in Western countries, the publication of codes of good governance and the promulgation of an important legal arsenal (the Sarbanes-Oxley Act, Financial Security Act). The purpose of such principles is to reinforce companies' obligations in terms of transparency of information and to develop the values of ethics and social responsibility of managers.In addition, this context inevitably put upfront the internal audit function, whose main mission is to make the value chain of financial information more reliable and to give assurance to shareholders and other stakeholders that their company is well under control and achieves the goals set. In fact, the Institute of Internal Auditors (IIA) defines the audit function as "an activity that helps companies achieve its objectives by evaluating, through a systematic and methodical approach, its business processes, risk management, control and corporate governance and making proposals to enhance its effectiveness ". This definition places the role of the internal audit function in corporate governance which, according to the agency's theory, appears as a mechanism for controlling and monitoring the behavior of the agent (manager) it is to verify that the managers have complied with all its contractual obligations.While it is clear that the practices of governance in developed countries have been the subject of many studies for several decades thus allowing a fairly complete knowledge of governance in European, Japanese or North American companies, in developing countries, on the other hand, research is scarce and, if it exists, is not widely known and remains little explored. However, these economies deserve special attention in terms of governance because they are characterized by a strong propensity for corruption but also mismanagement as well as the cumbersome and opaque modes of internal control of companies (Cohen, E., 2002 cited by Mendy 2010). Officials around the world recognize that corporate governance reform is vital for those developing countries seeking to attract investment and thereby strengthen their economies. Hence our research question: How does internal audit contribute to improving corporate governance in a developing economy? We chose as a field of study, the Moroccan companies.This communication aims to highlight the issues and specificities of internal audit as a mechanism of governance in the companies of an emerging economy such as Morocco. To answer our research question, we structured our communication in two parts: The objective of the first part is to understand the scope of the internal audit to perceive this function as a governance mechanism of the company. It can actually act both, in the words of Charreaux (2002), on the "enabling" dimension, but also on the "binding" dimension of corporate governance. The second part provides an empirical answer to our research, an exploratory study by face to face interviews (23 interviews) was conducted with nine companies in several sectors. The semi-directive interviews were conducted with the auditors as well as the directors and administrators. The first results of this study allowed us to conclude that all the conditions for the internal audit to actively contribute to the effectiveness of the governance system are not met in Moroccan companies. In the same way Corporate governance practices in Morocco are not a simple transposition of practices observed in developed countries, we have noted an invention of new rules adapted to the Moroccan context.
Keywords: 650; Corporate governance; Internal audit; Emerging economy